Implementasi Kebijakan Tata Cara Dan Persyaratan Permintaan Pemeriksaan Teknis Kriminalitas Tempat Kejadian Perkara Dan Laboratoris Kriminalistik Barang Bukti Kepada Laboratorium Forensik Polri Di Kepolisian Daerah Sumatera Selatan - Saputra, Aliyus; Mudasir, Mudasir; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to identify and analyze the Implementation of Policies on Procedures and Requirements for Requesting Criminal Investigations at the Crime Scene and the Criminalistics Laboratory for Evidence to the Bidlabfor Polda Sumsel. This research is a descriptive research with a qualitative approach. The data used is based on the type of quantitative data and qualitative data while based on the source is primary data and secondary data. The data collection instruments used were observation, interviews and documentation. The informants in this study were 1) the Forensic Laboratory of the South Sumatra Police (Subbarenmin as examiner of administrative requirements and sub-bid/investigator as examiner of technical requirements for evidence; 2) the Criminal Case Investigation Team for the service area of ​​Bidlabfor Polda Sumsel (South Sumatra Police, Lampung Police, Polda Jambi, Bengkulu Regional Police and Babel Islands Regional Police). Data analysis is a qualitative analysis with an interactive model. Based on the results of the study, it can be concluded that the implementation of the Policies on Procedures and Requirements for Requesting Criminal Investigations at the Crime Scene and the Criminalistic Evidence Laboratories for the Police Forensic Laboratory at the Regional Police of South Sumatra has been carried out in accordance with the procedures and provisions that apply in the Indonesian National Police Perkap No. 10 of 2009.